Estrategias educativas para la prevención del cáncer de cérvix en mujeres de edad fértil del Centro de Salud No.1 - Móran Hérnandez, Paola Maribel (2019)
This research was conducted at Health Center No. 1 in the city of Tulcán. The objective was to develop educational strategies for the prevention of cervical cancer in women of childbearing age. This work was conducted using a mixed approach, combining qualitative and quantitative paradigms, based on descriptive, correlational, and cross-sectional research, using methods such as historical-logical, inductive-deductive, and analytical-synthetic. These methods contributed to a better understanding of the current state of the problem and served as the basis for developing the proposal. A survey was used as a data collection technique, which allowed for obtaining real results in a population of 8,601 women of childbearing age, with a sample of 148 women.Among the main findings, it was diagnosed that there is no culture of cervical cancer prevention. Preventive measures are not defined, nor are any measures to be taken prior to performing a Pap smear. Furthermore, a group of women had never had this test, due to the lack of preventive initiatives, accompanied by other factors such as fear, embarrassment, lack of time, and the long wait for the data obtained from the exam. As a public health professional, interventions were made through promotion and prevention, the results of which were to strengthen knowledge about cervical cancer prevention, encourage women who had never had a Pap smear to do so, taking care of their own health, and thus reduce morbidity and mortality in the female population.